2009
DOI: 10.3201/eid1510.081040
|View full text |Cite
|
Sign up to set email alerts
|

Review of an Influenza Surveillance System, Beijing, People’s Republic of China

Abstract: This system enabled detection of the onset and peak of an epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 20 publications
3
75
0
Order By: Relevance
“…These studies reported levels of positive influenza A virus seasonal strain detection ranging from 25% in Peru to 40% in Greece (18,22). Our level of influenza A virus detection (33.1%) appears to be in agreement with previous published worldwide studies (17,22,30,41,42 Interestingly, the combination of two RT-PCR DNA microarray systems allowed us to detect not only influenza A virus strains but also 17 other common or newly discovered respiratory viruses in the same sample. This approach demonstrated that HRV and PIV were important causes of ILI, with 25 and 10.5% prevalence, respectively (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These studies reported levels of positive influenza A virus seasonal strain detection ranging from 25% in Peru to 40% in Greece (18,22). Our level of influenza A virus detection (33.1%) appears to be in agreement with previous published worldwide studies (17,22,30,41,42 Interestingly, the combination of two RT-PCR DNA microarray systems allowed us to detect not only influenza A virus strains but also 17 other common or newly discovered respiratory viruses in the same sample. This approach demonstrated that HRV and PIV were important causes of ILI, with 25 and 10.5% prevalence, respectively (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…1). Numerous previous studies detected the presence of influenza viruses in the respiratory tracts of ILI patients by use of real-time RT-PCR systems during 2007 to 2008 (18,30,41,42). These studies reported levels of positive influenza A virus seasonal strain detection ranging from 25% in Peru to 40% in Greece (18,22).…”
Section: Discussionmentioning
confidence: 93%
“…In Beijing, we established a comprehensive surveillance system with fifty five collaborating laboratories covering all 17 ), and those variables with P < 0.1 in univariate analysis were included in multivariate analysis. OR, odd ratio; CI, confidence interval; NA: not available (logistic regression could not be performed because of data distribution or small sample size); ICU, intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…This positivity rate is much lower than that reported from neighbouring and Asian countries like Pakistan (24%), China (30%), Bangladesh (10%), and Jordan (9%) (14)(15)(16)(17), which have similar sentinel surveillance systems, and may suggest some underestimation. Nonetheless, it should be noted that after more than 3 decades of war and conflict, the system was able to detect and respond successfully to the novel influenza virus circulating during the influenza A (H1N1) pandemic in 2009.…”
Section: Discussionmentioning
confidence: 41%